University Students’ Study Program Preferences Based on Career Motivation, Quantitative Ability, and Mathematical Reasoning - Firdaus, Ridwan Awalian; Lestari, Witri; Liberna, Hawa (Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2026)
This research aims to analyze students' study program preferences based on career motivation, quantitative ability, and reasoning ability. This type of research is quantitative correlational. The analysis uses multiple linear regression. The population comes from 12th-grade students of BOASH High School in the 2025/2026 academic year. The sampling technique used was stratified random sampling, with 210 respondents in 14 classes. The results of the study using SPSS show that the t-test for career motivation, quantitative ability, and reasoning ability are each less than the 0.05 significance level. This means that each variable has a significant influence on major preferences. The F-test produces a value less than 0.05. This means that career motivation, quantitative ability, and reasoning ability simultaneously influence major preferences. The multiple linear regression model obtained is Y = 7.303 + 0.426X1 + 0.337X2 + 0.227X3. It can be seen that all coefficients are positive, meaning that an increase in the independent variable will cause an increase in the dependent variable. The coefficient of determination obtained is R2 = 0.752, meaning that 75.2% of the variation in college study program preferences can be explained by career motivation, quantitative ability, and mathematical reasoning ability, while the remaining 24.8% is caused by other factors outside the research.